Rubies in the orchard : how to uncover the hidden gems in your business - Resnick, Lynda; Wilkinson, Francis (New York : Doubleday, 2009)
Lynda Resnick's marketing triumphs read like an encyclopedia of branding. In Rubies in the Orchard, she divulges her secrets for creating some of the world's most memorable and iconic brands, and the bull's-eye strategies to sell them.
"The POM Queen's secrets to building brands and marketing just about anything."--Jacket.
Includes index.
Keywords: Marketing; Advertising; Value; Business